2023
DOI: 10.3390/neurolint15020037
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Recurrent Glioblastoma as a Prognostic Factor in the Synergistic System of the Tumor Microenvironment

Abstract: Glioblastoma (GBM) is a common and highly malignant primary tumor of the central nervous system in adults. Ever more recent papers are focusing on understanding the role of the tumor microenvironment (TME) in affecting tumorigenesis and the subsequent prognosis. We assessed the impact of macrophages in the TME on the prognosis in patients with recurrent GBM. A PubMed, MEDLINE and Scopus review was conducted to identify all studies dealing with macrophages in the GBM microenvironment from January 2016 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 98 publications
0
31
0
Order By: Relevance
“…While we did not observe a correlation between IL13Ra2 expression and T-cell infiltration, RNA-Seq data revealed that the group with high IL13Ra2 expression exhibited lower immune and microenvironment scores. Recent research has highlighted the potential role of glioma-associated macrophages in glioblastoma progression and the formation of an immunosuppressive milieu within glioblastomas [ 59 , 60 ]. Likewise, prior studies have identified macrophages as crucial elements in shaping the non-inflammatory tumor environment in DIPG [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not observe a correlation between IL13Ra2 expression and T-cell infiltration, RNA-Seq data revealed that the group with high IL13Ra2 expression exhibited lower immune and microenvironment scores. Recent research has highlighted the potential role of glioma-associated macrophages in glioblastoma progression and the formation of an immunosuppressive milieu within glioblastomas [ 59 , 60 ]. Likewise, prior studies have identified macrophages as crucial elements in shaping the non-inflammatory tumor environment in DIPG [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study only analyzed somatic mutations and did not consider other genetic alterations, such as copy number variations and epigenetic modifications, which also play a role in GBM development and progression. Furthermore, the impact of the tumor microenvironment and immune cells, particularly macrophages, on glioma progression and survival has not been considered in our analysis [ 28 , 29 ]. Finally, we did not perform functional assays or in vivo models to validate the mutations of OBSCN or/and AHNAK2 in GBM patients, which makes it difficult to ascertain their clinical implications and their association with favorable survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 2 and Table 3 , we summarize some research articles where the authors studied cell-free miRNAs as non-invasive biomarkers for the diagnosis and prognosis of brain tumors [ 44 , 45 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Cell-free Mirnas As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%